CeO2 doped Pt/C as an efficient cathode catalyst for an air-cathode single-chamber microbial fuel cell. Issue 31 (9th March 2016) - Li, Ling; Wang, Mingkun; Cui, Ning; Ding, Yuedi; Feng, Qingling; Zhang, Wenming; Li, Xiaowei
Abstract : Incorporation of nanophase ceria into the cathode catalyst Pt/C was used as alternative cathode catalysts for the oxygen reduction reaction in an air-cathode single-chamber microbial fuel cell (SCMFC) for the first time. Abstract : Incorporation of nanophase ceria into the cathode catalyst Pt/C was used as alternative cathode catalysts for the oxygen reduction reaction in an air-cathode single-chamber microbial fuel cell (SCMFC) for the first time. Electrochemical results reveal that the ceria doped Pt/C catalysts exhibited a higher catalytic performance than the pure Pt/C catalyst. The highest voltage of 580 mV and the maximum power density of 840 ± 24 mW m −2 were achieved from the 3 wt% CeO2 doped Pt/C cathode, which was larger than that of the pure Pt/C cathode.